Effectiveness of Functional Strength Training Exercises Versus Neurodynamic Exercises on Balance and Gait of patients with Diabetic Peripheral Neuropathy - D., Mythili; K., Kotteeswaran; V., Balchandar (INTI International University, 2023)
Background: Diabetic neuropathy is one of the long-term complications of Diabetes Mellitus. Diabetic neuropathy symptoms include pain and numbness in the legs, feet and hands, causing decreased sensation, proprioception, reflexes, and strength in the lower extremities which affects balance and gait. Various interventions which are used by the physical therapist to minimize balance dysfunction and improve Gait in people with Diabetic Polyneuropathy. Approximately 50 percent of patients with diabetes will eventually develop neuropathy which leads to impairment in Balance and Gait. The Functional Strength Training improves the intermuscular and intramuscular synchronization through the neural control, thereby increases the muscle power by functional activities. Neurodynamic is the communication between different parts of the nervous system and mobilize the peripheral nervous system, it is a physical approach to the treatment of pain. This influences pain physiology via mechanical treatment of neural and the non-neural structures of the nervous system. Both Functional Strength Training and Neurodynamic exercises have influence on improving balance, gait and reduces the risk of fall. The aim of this study is to compare the effects of Functional strength training Versus Neurodynamic exercises on Balance and Gait of patients with Diabetic Peripheral Neuropathy. Methodology: 30 patients aged 40-80 years presenting with more than 7 years who were clinically diagnosed with Diabetic Peripheral Neuropathy were selected and assigned into two groups. Experimental group A received Functional Strength Training Exercises and Group B received Neurodynamic Exercises for 40 minutes, 5 days per week for a period of 4 weeks. Balance and Gait were assessed in terms of Berg Balance Scale and Functional Gait Assessment. Paired and unpaired ‘t-tests’ were used to determine significant differences in data among groups and between the groups. Results: A significant improvement in the values of Berg Balance Scale and Functional Gait Assessment was observed in Functional Strength Training Exercises as well as in Neurodynamic Exercises. Functional Strength Training Exercises showed statistically significant improvement in terms of BBS and FGA than the Neurodynamic Exercises. Conclusion: Both Functional Strength Training Exercises and Neurodynamic Exercises were found to improve the Balance and Gait in patients with Diabetic Peripheral Neuropathy. However, the Functional Strength Training showed more significantly improvement in Balance and Gait subsequently reducing fall and fall risk injury.